2014
DOI: 10.1109/thms.2014.2340578
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Singlemodal and Multimodal Face Recognition: A Survey

Abstract: High performance for face recognition systems occurs in controlled environments and degrades with variations in illumination, facial expression, and pose. Efforts have been made to explore alternate face modalities such as infrared (IR) and 3-D for face recognition. Studies also demonstrate that fusion of multiple face modalities improve performance as compared with singlemodal face recognition. This paper categorizes these algorithms into singlemodal and multimodal face recognition and evaluates methods withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 97 publications
0
33
0
1
Order By: Relevance
“…Former studies have shown that, when a large number of representative training images are available, computer algorithms are able to recognize even better than humans [6], [7], [25], [27], [33]. These algorithms, before recognizing, represent the face in the feature space, and perhaps because they are able to extract information from training images about the changes caused by different conditions they outperform humans in recognition [25].…”
Section: Introductionmentioning
confidence: 99%
“…Former studies have shown that, when a large number of representative training images are available, computer algorithms are able to recognize even better than humans [6], [7], [25], [27], [33]. These algorithms, before recognizing, represent the face in the feature space, and perhaps because they are able to extract information from training images about the changes caused by different conditions they outperform humans in recognition [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades the pattern recognition, biometrics and feature extraction became very popular research area among the researchers [1]- [4]. In this context, the face recognition problem can be viewed as a classification problem where one or more test images are compared with the face images stored in the databases.…”
Section: Introductionmentioning
confidence: 99%
“…methods can be classified into three main categories: (a) holistic approach, (b) feature based approach and (c) hybrid approach [1]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…al. [6] says that the performance of face recognition systems degrades with the variants like illumination, pose, and facial expressions. In their paper, they proposed 3D face recognition systems which contains 3D facial geometry information.…”
Section: Introductionmentioning
confidence: 99%